JESUITS PROFESSORS’ PROTAGONISM WITH THEIR EDUCATIONAL PROPOSAL CARRIED OUT AT CORDOBA DEL TUCUMAN UNIVERSITY IN THE 17 TH CENTURY - Vera de Flachs, María Cristina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
In this article, the performance of the first Jesuits professors of the Universidad de Córdoba del Tucumán during  17th century is rescued, inasmuch as, they with their ideals, utopias, academic ordering and ways to transmit their knowledge, were fundamental protagonists in the educational process of American youth. Trough their chairs, they dictated, they fulfilled the mandate of the Ratio and thought, and the values of the Order that became an alive example of that pedagogy that they tried to form men in science and religion.